THE ROLE OF EMOTIONAL REGULATION IN CLASSROOM BEHAVIOR AND ACADEMIC PERFORMANCE IN PRIMARY SCHOOL STUDENTS - Hafnidar; Dilshod Tursunov; Kabelo Dube (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Emotional regulation has emerged as a critical component of students’ socio-emotional development, particularly in primary school settings where behavioral adjustment and academic engagement are essential for effective learning. In classroom contexts, students are required to manage emotions such as frustration, anxiety, and excitement while responding to instructional demands and social interactions. Understanding the role of emotional regulation is therefore fundamental to explaining variations in classroom behavior and academic performance among young learners. This study aims to examine the role of emotional regulation in predicting classroom behavior and academic performance in primary school students. A quantitative correlational research design was employed involving primary school students from upper elementary grades. Data were collected using standardized emotional regulation scales, teacher-rated classroom behavior instruments, and documented academic performance records. Statistical analyses included descriptive statistics, correlation analysis, and regression testing. The results indicate that emotional regulation is significantly associated with adaptive classroom behavior and positively related to academic performance. Emotional regulation also emerged as a significant predictor of classroom behavior and learning outcomes, highlighting its central role in supporting effective learning processes. The study concludes that emotional regulation is a foundational skill that influences how students behave and perform academically in primary school. These findings emphasize the importance of integrating emotional regulation development into instructional practices and educational frameworks to foster both behavioral adjustment and academic success.